Gender Equality and Women’s Political Representation in Turkey - Ozdemir, Eylem (Advances in Social Sciences Research Journal, 2018)
Women’s status in political participation is one of the most visible signs to show gender equality level. A balanced representation of women in political decision-making and public management is an important condition for democracy and is of vital importance for the quality of public management. In this paper I will try to examine gender based features of political participation in Turkey and compare the situtation at national and local levels referring some statistics and documents of women organizations and government. Equality between women and men is recognised as a human right, an important condition for social justice and at the same time an indispensable and fundamental precondition for equality, development and peace. Even though numerous achievements were made in Turkey in this respect during the Republican Period, it is currently observed that, in practice, gender equality has not been reflected in social and political life. Although governments oficially accept that as an important condition for democracy it is still a long and difficult journey for women to have a de facto equality besides legal.